Step
*
1
of Lemma
bag-drop-co-restrict
1. X : Type
2. eq : EqDecider(X)
3. x : X
4. b : bag(X)
5. b = ({x} + bag-drop(eq;b;x)) ∈ bag(X)
⊢ (bag-drop(eq;b;x)|¬x) = (b|¬x) ∈ bag(X)
BY
{ (ApFunToHypEquands `Z' ⌜(Z|¬x)⌝ ⌜bag(X)⌝ (-1)⋅ THEN Auto) }
1
1. X : Type
2. eq : EqDecider(X)
3. x : X
4. b : bag(X)
5. b = ({x} + bag-drop(eq;b;x)) ∈ bag(X)
6. (b|¬x) = ({x} + bag-drop(eq;b;x)|¬x) ∈ bag(X)
⊢ (bag-drop(eq;b;x)|¬x) = (b|¬x) ∈ bag(X)
Latex:
Latex:
1.  X  :  Type
2.  eq  :  EqDecider(X)
3.  x  :  X
4.  b  :  bag(X)
5.  b  =  (\{x\}  +  bag-drop(eq;b;x))
\mvdash{}  (bag-drop(eq;b;x)|\mneg{}x)  =  (b|\mneg{}x)
By
Latex:
(ApFunToHypEquands  `Z'  \mkleeneopen{}(Z|\mneg{}x)\mkleeneclose{}  \mkleeneopen{}bag(X)\mkleeneclose{}  (-1)\mcdot{}  THEN  Auto)
Home
Index